POTENTIAL OF INNER BOARDING SCHOOLS SHARIA ECONOMIC DEVELOPMENT AT CIREBON KAMPEK SPECIAL BOARDING SCHOOL - Ahmad, Sirojudin; Nurzaman, Aji; Rohimah, Siti; Sinta, Dewi; Aditiya, Arif (Penerbit Lafadz Jaya, 2022)
Islamic boarding schools in Indonesia have an important role in forming an ideal and inclusive Muslim society. As an Islamic educational institution, Islamic boarding schools are also agents of significant social change. In the context of an increasingly developing sharia economy, Islamic boarding schools have great potential to contribute. First, Islamic boarding schools act as agents of social change in the field of sharia economics, teaching the values ​​and principles of Islamic economics to students and the surrounding community. Second, Islamic boarding schools can function as sharia business laboratories, where business practices that comply with sharia principles can be implemented and tested. Third, Islamic boarding schools become centers of sharia economic learning, providing education and training regarding the sharia economic system to the young generation of Muslims. Thus, Islamic boarding schools have the potential to support and develop the sharia economy in Indonesia, strengthening their role in the social and economic order of Muslim communities.